Common and well‐documented HLA alleles over all of Europe and within European sub‐regions: A catalogue from the European Federation for Immunogenetics. (February 2017) - Sanchez‐Mazas, A.; Nunes, J. M.; Middleton, D.; Sauter, J.; Buhler, S.; McCabe, A.; Hofmann, J.; Baier, D. M.; Schmidt, A. H.; Nicoloso, G.; Andreani, M.; Grubic, Z.; et al.
Abstract : Background: A catalogue of common and well‐documented (CWD) human leukocyte antigen (HLA), previously established by the American Society for Histocompatibility and Immunogenetics (ASHI), is widely used as indicator for typing ambiguities to be resolved in tissue transplantation or for checking the universality of any HLA allele in the world. However, European population samples, which are characterized by a substantial level of genetic variation, are underrepresented in the ASHI catalogue. Therefore, the Population Genetics Working Group of the European Federation for Immunogenetics (EFI) has facilitated data collection for an European CWD catalogue. Materials and Methods: To this end, 2nd‐field HLA‐A, ‐B, ‐C, ‐ DRB1, ‐ DQA1, ‐ DQB1 and ‐DPB1 data of 77 to 121 European population samples (21 571‐3 966 984 individuals) from 3 large databases, HLA‐net/Gene[VA], allelefrequencies.net and DKMS, were analysed. Results: The total number of CWD alleles is similar in the EFI (N = 1048) and ASHI (N = 1031) catalogues, but the former counts less common (N = 236 vs 377) and more well‐documented (N = 812 vs 654) alleles than the latter, possibly reflecting differences in sample numbers and sizes. Interestingly, approximately half of the CWD alleles reported by EFI were not reported by ASHI and vice‐versa, underlining the distinct features of the two catalogues. Also, although 78 common alleles are widely distributed across Europe, some alleles are only common within specific sub‐regions, showing regional variability. Conclusion: Although the definition of CWD alleles itself is affected by different parameters, calling for current updates of the list, the EFI CWD catalogue provides new insights into European population genetics and will be a very useful tool for tissue‐typing laboratories in and beyond Europe.